ANALISIS ANGGARAN BIAYA DAN REALISASI BIAYA PROYEK PEMBANGUNAN GEDUNG ASRAMA PUTRI DI YAYASAN DHARMA LAKSANA KOTA MATARAM - I WAYAN GRYA DHANENDRA; BAGUS WIDHI DHARMA S.; I GUSTI NGURAH OCTAVA S. (SOSIAL SAINS DAN TEKNOLOGI, 2023)
This study aims to analyze the budget and realization of project costs for the construction of a female dormitory building at the Dharma Laksana Foundation, Mataram City. The method in this study uses a type of comparative descriptive method with a quantitative approach. The type of data used is quantitative data, the data sources used are primary data and secondary data.The total budget for the construction of the girls' dormitory building at the dharma laksana foundation is Rp. 435,130,197, and when the construction was carried out there were material changes which caused a difference in the budget of Rp. 512,726 where this difference was a profit, but there was some additional work outside the construction of this girls' dormitory building where the extra budget was included in additional work